"Click" generation of a conjugated polymer library for SWNT dispersion. Issue 18 (7th August 2018) - Li, Kelvin; Kardelis, Vladimir; Adronov, Alex
ABSTRACT: Noncovalent functionalization of single‐walled carbon nanotubes (SWNTs) with conjugated polymers enhances SWNT processability and allows for selective dispersion of various SWNT species. Selective dispersions can be obtained by tuning the nature of the polymer, which can involve using various polymer backbones or side‐chains. However, a clear understanding of selectivity determinants is elusive, as the degree of polymerization (DP) has a large effect on SWNT selectivity. Additionally, preparing libraries of conjugated polymers with varying functionality while keeping DP consistent is difficult. Here, we report the utilization of a strained cyclooctyne‐containing conjugated polymer that serves as a versatile scaffold, enabling systematic preparation of a small library of conjugated polymers with different side‐chain functionality, while maintaining a consistent DP. The resulting polymers were used as dispersants for SWNTs, forming supramolecular polymer‐SWNT complexes that were characterized by UV‐Vis‐NIR absorption and Raman spectroscopy. In the series of polymers, we were able to probe the effect of small changes within the side chains, such as the incorporation of a carbonyl group or an aromatic unit, on the quality of the polymer‐SWNT dispersion. The results of these studies provide new insight into the factors that dictate the ability of a polymer to form strong interactions with SWNTs. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2053–2058 Abstract : A conjugated polymer library was prepared by strain‐promoted azide‐alkyne cycloaddition, allowing elucidation of the effect that small structural changes, such as the introduction of a ketone group, have on polymer interactions with carbon nanotubes.